Education and Menstrual Hygiene: Practice and Awareness among Women in Ramechhap District - Ghising, Dipak (Journal of Health Promotion, 2025)
Menstrual hygiene is a fundamental right in women's reproductive health influenced by several factors. This study examines the influence of education on menstrual hygiene and awareness among women in Ramechhap District. It specifically analyses the relationship between educational level and menstrual hygiene behaviors while taking into account control variables such as caste-ethnicity and religion. The study area comprised six wards in Khandadevi Rural Municipality, Ramechhap District, Nepal, and the sample comprised 351 female respondents. The secondary data were adopted from a 2025 baseline study report of the Community Development Society (CDS), Manthali, Ramechhap. The analysis employs binary logistic regression, which is fitted to the model at p